2017
DOI: 10.5350/sleep.hypn.2017.19.0134
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise-Induced Weight Loss Improves Self-Reported Quality of Sleep in Obese Elderly Women with Sleep Disorders

Abstract: Study Objective: Epidemiological studies have shown a close correlation between obesity and sleep disorders which threatens the quality of life in the elderly. Thus, the purpose of this research was to study the effect of the aerobic exercise (with the aim of decreasing obesity) on quality of sleep in obese elderly women. Method: 34 obese elderly women with sleep disorder recognized by Pittsburgh Sleep Quality Index (PSQI), were recruited purposefully from the Preventive healthcare Center and randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
2
25
0
2
Order By: Relevance
“…The result is consistent with Monleon who reported that a light aerobic exercise would alleviate the possible negative effects of sleep disturbances on psychomotor tasks (16). Besides, it has been well-documented that exercise can be considered as a non-invasive method leading to optimal status of sleep quality (19,20). According to a study, sleep loss can affect pre-frontal cortex metabolism, which negatively impairs the executive functions (21).…”
Section: Discussionsupporting
confidence: 85%
“…The result is consistent with Monleon who reported that a light aerobic exercise would alleviate the possible negative effects of sleep disturbances on psychomotor tasks (16). Besides, it has been well-documented that exercise can be considered as a non-invasive method leading to optimal status of sleep quality (19,20). According to a study, sleep loss can affect pre-frontal cortex metabolism, which negatively impairs the executive functions (21).…”
Section: Discussionsupporting
confidence: 85%
“…As shown in result section, there was also a decrease in WHR, PBF of exercise group after training intervention. This can be a logical reason for sleep improvement in experimental group as Taheri et.al (2017), Martin er al (2016) reported that fat mass decline especially internally is positively associated in better sleep quality (Martín et al, 2016;Taheri & Irandoust, 2017). In other words, decreasing the visceral fat of subjects can be effective in improvement of sleep indexes and consequently betterment of attention in the investigated subjects.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have focused on the sleep process in insomnia. Regular daytime exercise can increase melatonin secretion in and improve the sleep quality of patients with insomnia ( Taheri & Irandoust, 2018 ). Insomnia can also result in cognitive dysfunction because sleep may restore cognitive function and maintain attentional mechanisms ( Taheri & Arabameri, 2012 ).…”
Section: Discussionmentioning
confidence: 99%